Proposition of Media and Information Literacy Curriculum for Integration into Pedagogy in IITs - Unyial, Nirmal; Kaur, Baljinder (DESIDOC Journal of Library & Information Technology, 2018)
The purpose of the study is to identify the need of Media Information Literacy pedagogy in IITs through model curriculum if, proposed across the programme and courses. In this regard a survey was conducted with a well structured questionnaire for collection of data from targeted population with a sample of 1054 students of selected IITs of Northern India. Findings of the study demonstrate that 25 per cent to 30 per cent students welcome MIL curriculum for regular pedagogy. However, 60 per cent to 70 per cent students were of the opinion that MIL can enhance their critical thinking abilities for evaluating media messages which help the students to survive and thrive better in the digital world and prepares them for global communication and social participation.